V.I.P. care: Ethical dilemmas and recommendations for nurses - Perrone, Jennifer T (Nursing ethics, 2020)
Background:Not all patients are considered equal. For patients who are considered to be “very important persons,” care can be different from that of other patients with advantages of greater access to resources, special attention from staff, and options for luxurious hospital amenities. While very important person care is common and widely accepted by healthcare administration, it has negative implications for both very important person and non-very important person patients, supports care disparities and inequities, and can create serious ethical dilemmas for healthcare professionals. Very important person care can also result in negative care outcomes for its recipients.Objective:This article sought to explore the implications and ethical considerations of very important person care within the context of United States healthcare system, and integrate bioethical principles and American Nurses Association Code of Ethics for Nurses to influence recommendations for managing ethical dilemmas associated with very important person care.Method:A synthesis of the literature on very important person care was undertaken for this article.Ethical considerations:Ethical conduct was considered and respected when performing the literature review, referencing sources, and establishing authorship.Findings:According to the published literature, very important person care bares both positive and negative implications for patients, and negative implications for nurses. Nurses are the most affected by the demands from their administrators to provide special care and attention to patients in the “very important person” category and their families. Very important person care can be disruptive, disorienting, challenging, and stressful to nurses.Conclusion:While physicians and other healthcare professionals have commented on very important person care, limited work has been done in nursing. There have not been any empirical studies on very important person care. Therefore, in order to minimize the negative implications of very important person care, studies of this phenomenon are warranted. Exposing very important person care is important in the development of an ethical healthcare system. Moreover, understanding the ethical principles surrounding the concept of very important person care will empower nurses to effectively manage conflicts and ethical dilemmas that arise with very important person care.